GIST: gastrointestinal stromal tumors. - Uria, Sara (2012)
GIST (Gastrointestinal stromal tumors) are rare tumors of mesenchymal origin. The authors present a case of GIST in a 80 years old female with multiple co-morbilities, admitted with epigastric pain, gastrointestinal bleeding and heart failure decompensation.